The Physico-Chemical Quality of Streams and Channels Draining into River Rwizi, South Western Uganda - Atwebembeire, Jeninah; Bazira, Joel; Kagoro, Grace; Yatuha, Jane; Andama, Morgan; Lejju, Julius Bunny (Scientific Research Publishing, 2018)
There is an increased human population along the catchment area of river Rwizi who are engaged in various activities with potential to contaminate river Rwizi especially along the streams. Studies have been done to examine the physico-chemical quality of the mainstream river Rwizi in Mbarara Mu nicipality. However, the comprehensive source of contamination may be beyond the municipality and yet the streams have not been investigated to substantiate their contribution on quality degradation of the river and this formed the basis of the study. This study determined the physico-chemical parameters of streams draining into river Rwizi. Raw water was purposively selected from streams in the upstream, midstream and downstream sections of the river. Water samples were analyzed for 15 physico-chemical parameters including dissolved oxygen (DO), colour, turbidity, total suspended solid (TSS), total iron (Fe), phosphates ( 3 PO4 − ), alkalinity, magnesium (Mg), cal cium carbonate (CaCO3), temperature, pH, ammonium ( NH4 + ), electrical conductivity (EC), chloride (Cl) and nitrates (NO3). The water samples were analyzed following the standard methods of American Public Health Associa tion and standard operating manual (1985). The obtained values were also compared with the international Environmental Protection Agency (EPA, 2001) guidelines for water quality and the National Environment Manage ment Authority (NEMA, 1999) standards for waste water. The results showed that most of the streams in the downstream generally recorded the highest levels (p < 0.05) of the physico-chemical parameters followed by the mid stream and lastly the upstream. Streams in the downstream recorded the highest levels in most of the parameters tested i.e. bus park stream (tempera ture, 27.6˚C; colour, 431.17 TCU; TSS, 99.33 mg/l; alkalinity, 468.33 mg/l; Mg, 121.89 mg/l; CaCO3, 588.67 mg/l; Cl, 333.33 mg/l), Kikutu stream (tur bidity, 123.58 NTU; EC, 698 µs/cm; DO, 55.73 mg/l; 3 PO4 − , 12.85 mg/l), Ka kyeka upper (pH, 10.52; NH4 + , 46.67 mg/l), Rwentondo (Fe, 3.44 mg/l) and Kakyeka GBK (NO3, 10.83 mg/l). Most of the parameters downstream were higher than the EPA guideline (temperature, 25˚C; colour, 20 - 150 TCUs; TSS, 50 mg/l; alkalinity, 400 mg/l; Cl, 250 mg/l; DO, 5 mg/l; 3 PO4 − , 0.5 - 0.7 mg/l; pH, 5.5 - 9.0; NH4 + , 0.2 - 4 mg/l; Fe, 0.2 - 2.0 mg/l) and NEMA stan dards (colour, 300 TCUs; Mg, 100mg/l; DO, 5mg/l; 3 PO4 − , 10 mg/l; pH, 6.0 - 8.0). On the other hand, the streams in the upstream registered the lowest values of the parameters i.e. Kibimba (temperature, 17.28˚C; EC, 31 µs/cm; 3 PO4 − , 0.24 mg/l), Kasharara (colour, 15.17 TCU; TSS, 2.5 mg/l; pH, 6.23; al kalinity, 19.67 mg/l; DO, 9.99 mg/l; Mg, 4.41 mg/l; CaCO3, 23.17 mg/l) and Karungu (turbidity, 7.02 mg/l; Fe, 0.12 mg/l). Calcium carbonate hardness of the waters ranged from soft to excessively hard across the stream. The varia tions of the parameters detected in the streams in the downstream could reach adverse conditions if no intensive measures are taken to regulate the different anthropogenic activities within the catchment of river Rwizi.
Keywords: River Rwizi; Catchment; Water Quality; Physicochemical Parameters